The Bantu Presbyterian Church of South Africa : a history of the Free Church of Scotland mission - Duncan, Graham A. (Edinburgh University Press, 2022)
Examines the Free Church of Scotland Mission in South AfricaDraws substantially on primary and secondary sources from South Africa and ScotlandDemonstrates the exceptional activity of Scottish missionaries in the field of the development of Christian missionsIndicates the crucial role played by indigenous Christians in the growth of the mission. Establishes the history of South African Christianity in the context of racial segregation and apartheid.
Keywords: Bantu Presbyterian Church of South Africa.; Free Church of Scotland; Presbyterian Church -- Missions -- South Africa -- History.; Presbyterian Church -- South Africa -- History.; Presbyterian Church -- Scotland -- History.; Scotland -- Church history.; Église presbytérienne -- Afrique du Sud -- Histoire.; Église presbytérienne -- Écosse -- Histoire.; Écosse -- Histoire religieuse.; HISTORY / Europe / Great Britain; Presbyterian Church; Presbyterian Church -- Missions; Scotland; South Africa; Church history; History